2014
DOI: 10.3109/07357907.2014.883526
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 Enhances Cervical Cancer Cells Proliferation and JAK3/STAT5 Phosphorylation at Low Doses, While at High Doses IL-2 Has Opposite Effects

Abstract: The IL-2R signaling is critical for normal lymphocyte proliferation. However, the role of the IL-2 signaling in cervical cancer is not yet fully understood. We show that in IL-2R-expressing cervical cancer cells, JAK1 molecules are not phosphorylated. At low doses of IL-2, the constitutive phosphorylation of JAK3 and STAT5 increases in the tumor cells and decreases in lymphocytes, whereas the opposite occurs at high doses of IL-2. Using AG-490, the activation of JAK3 and the proliferation of cervical cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 47 publications
(63 reference statements)
2
34
0
Order By: Relevance
“…Secondly, in addition to STAT3, STAT5 has previously been shown to play an essential role during the productive HPV lifecycle [30,31]. In cervical cancer, STAT5 has been demonstrated to be over-expressed and to correlate with HPV infection [32,33]; however, if STAT5 plays a functional role in cervical cancer pathogenesis is unclear.…”
Section: Stat5 Is a Downstream Mediator Of Jak2 In Hpv+ Cervical Cancmentioning
confidence: 99%
“…Secondly, in addition to STAT3, STAT5 has previously been shown to play an essential role during the productive HPV lifecycle [30,31]. In cervical cancer, STAT5 has been demonstrated to be over-expressed and to correlate with HPV infection [32,33]; however, if STAT5 plays a functional role in cervical cancer pathogenesis is unclear.…”
Section: Stat5 Is a Downstream Mediator Of Jak2 In Hpv+ Cervical Cancmentioning
confidence: 99%
“…53 This notion is also supported by the STAT3 blockade data demonstrating that STAT3 has an important role in the expansion of Vγ2Vδ2 T cells by IL-23, but not IL-2. [80][81][82] It is interesting to demonstrate that TB can selectively impair IL-23 signaling but spare IL-2 effects on Vγ2Vδ2 T cells. 53,80 Such selective impairing of the IL-23 effect may occur as a result of persistent exposure of Vγ2Vδ2 T cells to phosphoantigen HMBPP or IL-23 during chronic TB infection.…”
Section: Immune Responses Of the Stat3 Pathway And Th17-like Cells Armentioning
confidence: 99%
“…JAK3 is an upstream regulator of STAT5 and STAT6. An accumulating data exercise revealed that inhibition of the JAK3 signaling could reduce cancer progression [37]. It is possible that the suppression of JAK/STAT signaling by gigantol should attenuate CSC in lung cancer.…”
Section: Discussionmentioning
confidence: 99%